2018
DOI: 10.1016/j.reth.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal regeneration with autologous periodontal ligament-derived cell sheets – A safety and efficacy study in ten patients

Abstract: BackgroundPeriodontitis results in the destruction of tooth-supporting periodontal tissues and does not have the ability to heal spontaneously. Various approaches have been introduced to regenerate periodontal tissues; however, these approaches have limited efficacy for treating severe defects. Cytotherapies combine stem cell biology and tissue engineering to form a promising approach for overcoming these limitations. In this study, we isolated periodontal ligament (PDL)-derived cells from patients and created… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
127
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 173 publications
(127 citation statements)
references
References 33 publications
0
127
0
Order By: Relevance
“…For example, an autologous myoblast sheet which was generated from skeletal muscle was used and transplanted to the lateral surface of the dilated heart of a patient suffering from dilated cardiomyopathy (DCM;Sawa et al, 2015). It was also used to reconstruct defects of the esophagus (Yamaguchi et al, 2017), middle cavity of the ear (Yamamoto et al, 2017), lung (Kanzaki, Takagi, Washio, Kokubo, & Yamato, 2017), periodontal tissue (Iwata et al, 2018), and the cornea (Nishida et al, 2004). For the cornea, this method has mostly been used for corneal epithelial cell and limbal epithelial stem cell transplantation in patients with unilateral stem cell deficiency (Umemoto, Yamato, Nishida, & Okano, 2013).…”
mentioning
confidence: 99%
“…For example, an autologous myoblast sheet which was generated from skeletal muscle was used and transplanted to the lateral surface of the dilated heart of a patient suffering from dilated cardiomyopathy (DCM;Sawa et al, 2015). It was also used to reconstruct defects of the esophagus (Yamaguchi et al, 2017), middle cavity of the ear (Yamamoto et al, 2017), lung (Kanzaki, Takagi, Washio, Kokubo, & Yamato, 2017), periodontal tissue (Iwata et al, 2018), and the cornea (Nishida et al, 2004). For the cornea, this method has mostly been used for corneal epithelial cell and limbal epithelial stem cell transplantation in patients with unilateral stem cell deficiency (Umemoto, Yamato, Nishida, & Okano, 2013).…”
mentioning
confidence: 99%
“…Cell sheet technology has a great advantage in that it can transplant appropriate stem/progenitor cells for tissue regeneration of target site as a uniform tissue, and can be used clinically for diseases and injuries in various tissues 31,32 . Different types of cell sheets, such as cartilage, esophagus epithelium and myocardium, can be easily made using tissue-derived stem/progenitor cells [39][40][41] , and a current advance in this field can create transplantable cell sheets, including retinal pigment epithelium and corneal epithelium, using the induced pluripotent stem (iPS) cells 42,43 .…”
Section: Discussionmentioning
confidence: 99%
“…Scaffold-free cell sheet engineering has been applied in regeneration of such tissues as cornea, heart, esophagus, cartilage, liver and periodontal 31 . A PDL cell sheet for the regeneration of periodontal tissue is now at the stage of clinical therapy for periodontal disease 32 . Although this technology contributes to partial tissue repair, a single cell sheet cannot sufficiently regenerate a large-scale tissue injury 33 .…”
mentioning
confidence: 99%
“…Retained native endogenous cell adhesion proteins provide several strategic advantages for cell sheet engraftment and retention at target tissues. Over 15 years of clinical data support enhanced therapeutic properties for autologous‐sourced cell sheets through increased cell retention at target tissues (Ebihara et al, 2012; Iwata et al, 2018; Kanzaki, Takagi, Washio, Kokubo, & Yamato, 2017; Nishida et al, 2004; Ohki et al, 2012; Sawa et al, 2015; Yamaguchi et al, 2017; Yamamoto et al, 2017). Recently, several preclinical studies have also reported MSC sheet use in wound healing, heart, and pancreas regeneration (Kato et al, 2015; Kim et al, 2018; Miyahara et al, 2006).…”
Section: Introductionmentioning
confidence: 99%